Qualidade de Vida no Trabalho (QVT): um estudo de caso com alunos estagiários de um curso de administração em uma instituição pública de nível superior - Nascimento, Fernanda Ferreira Lemos do (2019)
Changes in the world of work brought new ways of thinking about the worker and the search for well-being emerged, making Quality of Life at Work (QWL) a more present theme in the organizational world. Given this context, this research aims to analyze the Quality of Life at Work (QWL) of trainee students of a business course in a higher level public institution based on the Walton model. The research is characterized as a quantitative research, having been applied a structured questionnaire with 63 student interns. The results showed that criteria such as the use of development and skills had low satisfaction, but that there are criteria such as social integration and constitutionalism have a high satisfaction on the part of the participating trainees. As a whole, interns are satisfied with QWL in the organizations in which they are interns, however, actions are still needed by organizations to qualify interns and thus develop well-being at work.